(untitled) (Journal of the College of Basic Education, 2022)
The university is considered as a pioneer scientific edifice in the community, as it contributes to the overall and activities to achieve the general purposes of the community and exercising the foundation’s role in various community development programs, and the ability of the university to exercise, carry out and achieve its functions and objectives is significantly linked with the availability of appropriate regulatory of conditions in the forefront of the adoption of an administrative system that is flexible enough in dealing with internal and external changes and response degree more rational and realistic, and can therefore be achieved proceed orderly and gradual toward administrative decentralization, as it "helps manner decentralized the openness of educational institution more heavily on their local environment and enhance their contribution to the social, economic and cultural development," and directing its programs towards meeting local needs realism (Arafah 2011.179). This calls for reconsideration of the administrative organization of the University, according to the formula and the level of appropriate administrative decentralization, to ensure the effectiveness of its role in development programs and take into account the scientific, environmental privacy under fair central control. It illustrated that the problem of current study as indicated by the National Congress for the reform of higher education and scientific research to the need of the university to administrative decentralization to ensure the ease of work and implementation of its tasks, and that the administrative system suffers some of the administrative problems associated with the centrality of the university administration (May, .2014, 2-3). The current study aims at identifying some of the requirements for the decentralized management of Iraqi universities with regard to the cognitive aspect, legislative, regulatory, and determined public universities in Baghdad for the academic year 2015- 2016 A.D. To achieve the aim of the study, a questionnaire has been prepared consisted of (95) items distributed over three areas: cognitive requirements of (19) items and legislative requirements (19) items and regulatory requirements (57) items applied as the final method using Delphi technique by two rounds on a sample of experts who have been chosen through the sharing way by (0.3) percentage among the members of the community of the study (82) academics and senior leaders, and using the Fisher equation and the percentage in estimating the responses respondents and the adoption rate of agreement (90%) as a minimum to accept the item, it is concluded that there must be a need to provide workers in the university administration to know comprehensive decentralization content and style of its liabilities and utility management in achieving organizational goals effectively, as well as the need to adopt appropriate legislation and regulatory changes to this trend and implement an objective and rational way based on the facts of and requirements. The researcher has concluded that cognitive requirements and a clear priority among other requirements they represent the bedrock upon which the decentralized administrative organization of the University and unjustified attain the goals of the administrative legislation and its effectiveness in this area. To ensure the effectiveness of the adoption of the current search results provide the researcher recommends should be the real will and serious desire among the central authority of the Ministry of Higher Education and Scientific Research leadership to adopt all administrative slant pattern to some extent about the decentralized manner in the university administration. Complementing the trends of the study in other areas, the researcher suggests a study aimed at identifying trends university leaders about the decentralized manner in university administration and other targets defined for the development of the ability of university leaders, according decentralized management style training needs.